A Standardized Nurse Initiated Protocol to Improve Management of Severe Hypertension in Pregnancy [29L]. (May 2017) - Miller, Michael J.; Butler, Patricia; Drake, Elizabeth; Taylor, Anne; Lutgendorf, Monica A.
Abstract : INTRODUCTION: Hypertensive disorders are a leading cause of morbidity and mortality. We developed a standardized nurse driven hypertensive protocol to improve management in pregnancy. METHODS: We developed a standardized nurse initiated protocol for management of severe hypertension. The protocol used nifedipine, hydralazine or labetalol sequentially. Data on time from severe blood pressure (BP) to treatment with medication, effect of treatment, and BP monitoring was collected for 3 months prior to the protocol and compared to data after. RESULTS: We collected data on patients before (n=47) and after the protocol (n=37). The mean time to treatment of severe BPs was significantly shorter after protocol implementation (19.6 minutes), compared to before (36.9 minutes), t=3.1, p=0.002. There was also a significantly lower mean time to repeat BP (12.8 minutes) after protocol implementation compared to before (15.7 minutes), t=2.3, p=0.02, and the maximum time to repeat BP measurement decreased, from 300 minutes before to 76 minutes after. We also noted more women (89.5%) were treated within 1 hour after the protocol compared to 35% before the protocol and more women were given oral nifedipine (67%) after the protocol compared to only 4% prior to the protocol. However, there was no significant difference in mean time to blood pressure control after protocol implementation (50.3 minutes) comparted to before (67.5 minutes), t = 1.8, p = 0.08. CONCLUSION: Implementation of a standardized protocol for the treatment of hypertensive emergency decreased time to treatment, decreased variation and decreased maximum time to repeat BP measurement.